2020
DOI: 10.1111/raq.12508
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pest and disease management in aquaponics: A metadata‐based review

Abstract: Aquaponics has the potential to produce sustainable, high‐quality food through integration of hydroponics and aquaculture, but its commercialization is stalled by bottlenecks in pest and disease management. We reviewed integrated pest and disease management steps and techniques in hydroponics to qualify as suitable techniques for different aquaponic designs. Non‐chemical prophylactic measures are highly proficient for pest and disease prevention in all designs. Still, the use of chemical control methods remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 180 publications
(263 reference statements)
1
18
0
Order By: Relevance
“…We consider this term to be inappropriate and counterintuitive in that subsystem coupling is the very nature of the aquaponic principle. The subsystems are decoupled by interrupting the connection between both units in the event of a production break, maintenance, pest management, 105 or accident. In the dichotomy, ‘coupling’ is used according to its sense: ‘water and nutrient savings can be established by coupling water streams between interacting processes’ 6 whereas ‘decoupling’ has rather the sense of ‘detached’, as is shown, for example, in ‘these convenient fuels have allowed us to decouple human demand from biological regeneration’ 106 .…”
Section: Terms: On‐demand Coupled Vs Decoupled Aquaponicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider this term to be inappropriate and counterintuitive in that subsystem coupling is the very nature of the aquaponic principle. The subsystems are decoupled by interrupting the connection between both units in the event of a production break, maintenance, pest management, 105 or accident. In the dichotomy, ‘coupling’ is used according to its sense: ‘water and nutrient savings can be established by coupling water streams between interacting processes’ 6 whereas ‘decoupling’ has rather the sense of ‘detached’, as is shown, for example, in ‘these convenient fuels have allowed us to decouple human demand from biological regeneration’ 106 .…”
Section: Terms: On‐demand Coupled Vs Decoupled Aquaponicsmentioning
confidence: 99%
“…The subsystems are decoupled by interrupting the connection between both units in the event of a production break, maintenance, pest management, 105 or accident. In the dichotomy, 'coupling' is used according to its sense: 'water and nutrient savings can be established by coupling water streams between interacting processes' 6…”
Section: Terms: On -Demand Coupled Vs Decoupled Aquap Onic Smentioning
confidence: 99%
“…Garlic doesn't have insect problems, basically it is an insect repellent crop. Attack of thrips was observed in hydroponic cultivation of garlic which can be controllable (Folorunso et al, 2021). Pest control is necessary to prevent damage to the seedlings and producing plants.…”
Section: Garlic Productionmentioning
confidence: 99%
“…Therefore, there is a need to establish control methods with little or no negative influence on plants, fish, and beneficial bacteria. In previous studies focused on identifying an integrated pest and disease management suitable for aquaponics (Folorunso et al, 2021), it was found that existing commercial biological controls are natural remedies for aquaponics pests and could pose little or no harm to non-target organisms. On the other hand, pathogen management still relies on chemical controls, which can pose high toxicity risk to fish and beneficial bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical fungicides have primarily been most widely used control mechanisms in stand-alone hydroponics or field agriculture. But, as stated, spray drifts of fungicides in hydroponics units can cause harmful effects to fish and beneficial bacteria in coupled aquaponics where the water is recircled back to the fish and the biofilter or limit the water reuse capacity of decoupled aquaponics systems (Folorunso et al, 2021;Rasǩovićet al, 2021). Thus, consensus efforts are currently being channeled towards developing control approaches with little or no effects on non-target organisms.…”
Section: Introductionmentioning
confidence: 99%